Creación de un modelo de gestión que contribuya al desarrollo del cantón Portoviejo como destino turístico inteligente (DTI) - De La Torre Zambrano, José David (2023)
This research was made with the objective of contributing to the development of Portoviejo as a Smart Tourist Destination through the proposal of a tourism management model that allows the destination to efficiently manage the territory's resources. For the purposes mentioned above, a non-experimental exploratory level research with a mixed approach is structured, based on documentary-bibliographic and field research. The research was carried out in three steps: the first one consisted of carrying out a situational tourism diagnosis to know the current situation of the territory; The second part carried out the analysis of the tourism actors in the Portoviejo canton and ended with the proposal of the tourism management model to convert Portoviejo into a DTI. It is evident that, despite the numerous potentialities, the canton presents extensive problems in terms of management and articulation; Also, it is determined that there is a predisposition from the public, private and academic sectors to increase joint actions for the improvement of the canton. It was also found that in relation to DTI the destination is below average, with greater shortcomings in the axes of sustainability and accessibility, making effective intervention necessary. Finally; A tourism management model was proposed that allows it to be a dynamic tool which substantially contributes to the efficient management of the 5 axes of a DTI such as sustainability, governance, accessibility, technology and innovation to thus help the competent entities to Transition into a smart tourist city.